Street sweeping in Ibadan: Urbanising Yoruba traditional environmental sanitation practice (2014)
Traditional African societies possess indigenous knowledge systems . which promote' affordable, effective, socially acceptable and sustainable community-based environmental sanitation and hygiene. One of the age-long and tested indigenous sanitation practices of the Yorubas of West Africa is .the regular sweeping of their housing areas .including the streets and footpaths. This practice is being promoted in Ibadan by the Oyo state government as part of the environmental sanitation policy. This paper examines the effects of street sweeping activity on the quality of-streets; the public perception and the challenges facing street sweepers in Ibadan. It presents the result of a questionnaire survey of street sweeping practice carried out in 2011 along six of the fourteen dual carriage ways which traverse the five metropolitan local government areas of Ibadan. A total of 150 buildings along the streets were sampled, while 28 of the street sweepers, four street sweeping contractors and 12 officials of the Ministry of Environment and Habitat were interviewed. The study revealed that organised sweeping of streets has made them clean and created jobs for the citizens. Manual street sweeping is a cheap, effective, timeless and sustainable strategy that should be adopted by governments to improve the environmental quality of urban streetscape.